Engineering of thienothiophene-based conjugated molecules for the development of efficient P-type semiconductor - Abe, Yuichiro (2017)
In order to reduce the cost of energy production from clean and renewable energy source, next-generation solar cells have been extensively studied. Amongst the candidates for the next generation solar cells, organic solar cells have the advantage of a higher degree of freedom in terms of materials design and selection. Decades of research in the field has resulted in impressive power conversion efficiency (PCE). However, the materials development relies heavily on trial-and-error method due to the lack of good understanding of how to translate the molecular structure to the solid-state structure in devices. In this paper, small molecules having pi conjugated backbones have been synthesized and their properties have been studied in an attempt to establish the design principles of efficient organic semiconductors for the application in organic photovoltaic (OPV) devices.